The Digitalisation of Political Engagement in Nigeria - Adeyinka , Foluso M.; Ijaiya, Tahir Adekunle (Kashere Journal of Politics and International Relations, 2024)
Political participation and engagement are essential pillars of participatory democracy and allow citizens to exercise their power to steer the affairs of the country. Since the beginning of the century, digital technology has, however, impacted every aspect of human activities, including politics, especially with the adoption of digital tools for political participation and engagement. The study used secondary data to examine the political use of digital technology (especially the internet and social media) and its associated dangers in Nigeria. The study found that, in Nigeria, digital technology served as an emancipatory and empowerment tool that helps citizens participate in politics, especially during elections and protests, and in ways that traditional means cannot afford. This is evident in the role digital technology played during the 2011, 2015, 2019, and 2023 elections as well as during the 2012 Occupy Nigeria protest, 2014 Bring Back Our Girls Campaign, and 2020 EndSARS protest. At the same time, digital technology has been adopted by actors with malicious intent to spread misinformation and by the government to repress and censor Nigerians, which is detrimental to their right to privacy and freedom of association and speech. Evidence shows how public officials and private citizens spread misinformation, especially during political crisis. Evidence also abounds on government’s attempt to procure surveillance and censorship devices, pass bills on regulating online participation, and illegal arrest of journalist, citizens, and dissidents for expression their political opinion. This underscores the complex and nuanced nature of the digital-political landscape in Nigeria.